The Effect of Cash Holding, Leverage, and Company Size on Profit Quality - Adissya Hawalia Husni; Elprina Sarah Azahra (Journal of Accounting and Auditing, 2026)
Objective – This study aims to obtain empirical evidence on the Influence  of Cash Holding, Leverage, and Company Size on Profit Quality. Design/methodology/approach – This study uses a quantitative approach with panel data. The research sample consisted of 42 companies in the technology and industrial sectors listed on the Indonesia Stock Exchange during the 2022–2024 period, resulting in a total of 126 observations (42 companies during the three-year observation period). Data analysis was carried out using panel data regression with a Random Effect Model (REM) approach using EViews 9. Findings – The results of the study show that Cash Holding does not have a negative effect on Profit Quality. Meanwhile, Leverage has a negative effect on the Quality of Profit and Company Size has a positive effect on the Quality of Profit. Limitations/Implications of Research – The first limitation of this research is the type of data used in this study, namely secondary data obtained from the annual report published by the company. However, the data listed is incomplete even though it is mandatory to upload financial statements every year. Furthermore, this study has limitations on the sample from only 112 to 42 samples, while the rest is because the annual report data is incomplete and the company suffers losses. And finally, this study was conducted over a certain period of time, namely 2022-2024, which may not be for long-term analysis. However, the findings of this study are expected to be a consideration for investors and management in assessing the quality of company profits, especially in the technology and industrial sectors which have high levels of volatility. JEL : G34, M14, J16, Q56